A secondary battery
By using triphenyl phosphorus oxide and sulfonyl-containing compounds as electrolyte additives in lithium-ion secondary batteries, combined with optimizing the density design of positive and negative electrodes, the problem of insufficient charging capacity of lithium-ion secondary batteries under high and low temperature conditions is solved. , achieving improved battery performance balance and reduced lithium evolution phenomenon.
Patent Information
- Application Number
- CN201911241363.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-12-06
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2039-12-06
AI Technical Summary
In the process of increasing the negative electrode density to increase the volume energy density, the power characteristics and charging capacity are difficult to take into account, especially in high and low temperature conditions, the charging capacity is poor, and the lithium-ion secondary battery performance is caused by the negative electrode interface lithium analysis phenomenon. Accelerate deterioration.
Triphenylphosphorus oxide and sulfonyl-containing compounds are used as electrolyte additives, and combined with optimized density design of the positive and negative electrodes, ensuring that the battery is both high-temperature characteristics and low-temperature charging capacity, and suppressing the increase in the negative electrode impedance by limiting the dosage and structure of the additives. and lithium excretion phenomenon.
Under high negative electrode density conditions, the battery can maintain good high-temperature characteristics and low-temperature charging capabilities, reduce the negative electrode lithium evolution phenomenon, improve overall performance balance, and meet the usage requirements.
Smart Images

Figure BDA0002306329760000051 
Figure BDA0002306329760000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a secondary battery. Background Art
[0002] In recent years, the popularity of portable electronic devices such as mobile phones and laptops has promoted the demand for high-energy-density secondary batteries. Among the many secondary batteries, lithium-ion secondary batteries that achieve energy conversion by embedding and extracting lithium ions have higher energy density than lead-acid batteries and nickel-metal hydride batteries. Since their introduction, they have developed particularly rapidly, and their application areas include digital products, power tools, electric vehicles, communication base stations, and grid energy storage.
[0003] Secondary batteries mainly include positive electrodes, negative electrodes, separators and electrolytes. In recent years, the technical requirements for lithium-ion secondary batteries have become increasingly higher. For example, automotive start-stop batteries are required to have excellent cycle performance, power characteristics, high-temperature storage characteristics, low-temperature fast charging capabilities, etc., which are difficult to develop. In many application areas, people expect batteries to occupy a smaller volume to achieve portability or functional diversification of terminal devices. By increasing the density of the positive and negative electrode sheets of the battery (also known as compaction density), the volume energy density of the battery can be increased, but this will cause the power characteristics of the battery to deteriorate and the charging capacity to decrease.
[0004] Existing lithium-ion secondary batteries generally use carbon (graphite is the most commonly used) and silicon (and its oxides) materials as negative electrode active materials. In the process of charging and discharging, the negative electrode active materials easily react with the electrolyte, resulting in the decomposition of the electrolyte. Generally, additives are used to form a solid electrolyte interface film (SEI) on the surface of the negative electrode to inhibit the decomposition reaction of the solvent molecules in the electrolyte. By adding additives with negative electrode film-forming effects (such as vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone) to the electrolyte, it can play a role in forming a film on the surface of the carbon and silicon negative electrodes. Using oxides containing transition metal ions (such as LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 In lithium-ion secondary batteries using LiCoO2 or LiNi as the positive electrode active material, the dissolution of transition metal ions and their deposition on the negative electrode surface will lead to deterioration of battery performance. 0.5 Co 0.2 Mn 0.3When O2 is used as the positive electrode active material, in order to obtain a higher battery capacity, the charge cutoff voltage is sometimes set to 4.3V or higher (the conventional value is 4.2V). In this high voltage environment, the electrolyte is more susceptible to oxidative decomposition reactions. Therefore, the protection of the positive electrode surface of the battery should also be taken seriously. Positive electrode film-forming additives are generally used to inhibit the oxidative decomposition of the electrolyte. Commonly used positive electrode film-forming additives include sulfonyl compounds (such as 1,3-propane sultone, 1,3-(1-propylene) sultone), phosphates (such as lithium difluorophosphate), phosphites, and the like.
[0005] In order to achieve a higher volume energy density for the battery, the active material load of the positive and negative electrodes is generally increased through material design and battery manufacturing process optimization, such as by increasing the compaction density of the positive and negative electrodes, so that the battery can achieve a higher capacity (energy) under a certain volume. However, as the active material load in the electrode increases, the power characteristics of the battery will deteriorate. Among them, the increase in the negative electrode active material load will lead to a decrease in the battery's charging capacity. For commercial lithium-ion batteries, the density of the negative electrode excluding the current collector (referred to as the negative electrode compaction density) is generally 1.45-1.65g / cm 3 Under the condition of higher negative electrode compaction density, it is more difficult to make the battery have better charging capacity.
[0006] In practical applications, in order to make the battery have better high-temperature characteristics, a higher dose of film-forming additives is added to the electrolyte. A problem that follows is that the battery's charging capacity decreases. This problem is particularly obvious under low temperature conditions. A simple way to judge the charging capacity is to observe the negative electrode interface. If there is white attachment on the negative electrode interface after the battery is fully charged and disassembled, this phenomenon is called "lithium deposition". Negative lithium deposition will lead to accelerated deterioration of battery performance.
[0007] For secondary batteries with a high negative electrode density, it is very difficult to take into account both high-temperature characteristics and low-temperature charging capabilities. Summary of the invention
[0008] The technical problem to be solved by the present invention is to provide a battery with high negative electrode density, which can take into account both the high temperature characteristics and low temperature charging capability of the battery.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is:
[0010] A secondary battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte comprises a lithium salt, an organic solvent and an additive, wherein the additive comprises triphenylphosphine oxide and a sulfonyl compound, wherein the added mass of the triphenylphosphine oxide is 0.1% to 2.5% of the total mass of the electrolyte, wherein the sulfonyl compound has a ring structure and has 1 to 3 carbon atoms, wherein the added mass of the sulfonyl compound is 0.1% to 3% of the total mass of the electrolyte, wherein the negative electrode comprises a negative electrode active material and a negative electrode current collector, wherein the density of the negative electrode except the negative electrode current collector is not less than 1.55 g / cm 3 .
[0011] Preferably, the sulfonyl-containing compound is one or more of 1,3-propane sultone, 1,3-(1-propylene) sultone, vinyl sulfate, propylene sulfate, and vinyl sulfite.
[0012] Preferably, the added mass of the triphenylphosphine oxide is 0.5% to 2% of the total mass of the electrolyte.
[0013] Preferably, the added mass of the sulfonyl-containing compound is 0.5% to 2.5% of the total mass of the electrolyte.
[0014] Preferably, the density of the negative electrode other than the negative electrode current collector is not less than 1.6 g / cm 3 .
[0015] Preferably, the positive electrode comprises a positive electrode active material and a positive electrode current collector, and the density of the positive electrode excluding the positive electrode current collector is not less than 3 g / cm 3 .
[0016] Preferably, both the positive electrode and the negative electrode are capable of absorbing and desorbing lithium ions.
[0017] Preferably, the additive further comprises a sulfonyl-containing compound having a chain structure.
[0018] Preferably, the additive further comprises one or more of lithium difluorophosphate, lithium difluorobisoxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0019] Preferably, the lithium salt is one or more selected from lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, anhydrous lithium perchlorate, lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethylsulfonate, lithium bis(oxalatoborate), lithium mono(oxalatobis(fluoroborate))imide.
[0020] Preferably, the organic solvent is one or more of ethylene carbonate, propylene carbonate, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methylpropyl carbonate, methyl propionate, ethyl propionate, propyl propionate, methyl acetate, ethyl acetate, propyl acetate, methyl butyrate, ethyl butyrate, propyl butyrate, cyclopentane, diethylene glycol dimethyl ether, and triethylene glycol dimethyl ether.
[0021] It should be noted that the structure of the film-forming sulfonyl compound has a great influence on the battery performance, and its function is to enable the battery to have better high-temperature performance, but its high dosage will cause the battery charging capacity to decrease. The present invention combines triphenylphosphine oxide with a positive electrode protection effect with a film-forming additive sulfonyl compound, and limits the structure of the sulfonyl compound and the dosage of the two additives. Its function is to make the battery performance more balanced and meet the use requirements even under the condition of a higher negative electrode density.
[0022] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0023] Under the condition of relatively high negative electrode density, the secondary battery of the present invention can still take into account both high temperature characteristics and low temperature charging capability. DETAILED DESCRIPTION
[0024] The present application is described in detail below in conjunction with the embodiments, but the present application is not limited to these embodiments. Unless otherwise specified herein, "%" represents mass percentage and ratio represents mass ratio.
[0025] Embodiment 1:
[0026] [Manufacturing of positive electrode]
[0027] Weigh LiNi according to the mass ratio of 90:5:5 0.8 Co 0.1 Mn 0.1 O2, conductive carbon black and PVDF, add appropriate amount of NMP, stir thoroughly to obtain positive electrode slurry. The positive electrode slurry is coated on aluminum foil, rolled and cut after drying to obtain positive electrode. The density of the positive electrode excluding the current collector (referred to as positive electrode compaction density) is 3.5g / cm 3 .
[0028] [Manufacturing of negative electrode]
[0029] Graphite, styrene-butadiene rubber and carboxymethyl cellulose were weighed in a mass ratio of 95:3:2, and an appropriate amount of deionized water was added and stirred thoroughly to obtain a negative electrode slurry. The negative electrode slurry was coated on a copper foil, and after drying, it was rolled and cut to obtain a negative electrode. The density of the negative electrode excluding the current collector (referred to as the negative electrode compaction density) was 1.65 g / cm 3 .
[0030] [Preparation of non-aqueous electrolyte]
[0031] Ethylene carbonate (EC) and diethyl carbonate (EMC) were mixed in a mass ratio of 3:7 to obtain a mixed solvent, and lithium hexafluorophosphate was dissolved therein at a concentration of 1.15 mol / L. 0.5% of triphenylphosphine oxide (TPPO) and 0.5% of 1,3-propane sultone (PS) based on the total mass of the electrolyte were added to the lithium hexafluorophosphate solution, and after complete dissolution, a non-aqueous electrolyte was obtained.
[0032] [Battery Manufacturing]
[0033] The positive electrode, negative electrode and non-aqueous electrolyte are used, a PE separator with a thickness of 20 microns is selected, and a winding process is adopted to manufacture a soft-pack battery with a model of 053048.
[0034] [Battery performance test]
[0035] The battery was charged and discharged at a rate of 0.1C, degassed and sealed; then charged and discharged at a rate of 0.2C for one week (the voltage range was 3.0 to 4.25V, the same below).
[0036] The high temperature storage performance test is to first charge the battery at 0.5C constant current to 4.25V at 25℃, charge it at constant voltage until the current drops to 0.05C, and then store the battery in a 60℃ oven for 14 days. Test the internal resistance of the battery (fully charged) before and after storage. Internal resistance change rate = [(internal resistance after storage - internal resistance before storage) / internal resistance before storage] * 100%.
[0037] The high temperature cycle performance test is to charge and discharge the battery at 1C for 500 cycles at 50°C and calculate the capacity retention rate. Capacity retention rate = (500-cycle discharge capacity / first-cycle discharge capacity) * 100%.
[0038] The low-temperature charging capacity test is to charge the battery at 2C constant current to 4.25V at 5℃, and then charge it at constant voltage until the current drops to 0.05C. After the battery is left at room temperature for half an hour, it is disassembled in a dry room to observe the negative electrode interface condition.
[0039] Embodiment 2~5, comparative example 1~5:
[0040] The battery was manufactured in the same manner as in Example 1, except that the additives in the electrolyte and the negative electrode compaction density were changed. The battery performance test was carried out in the same manner as in Example 1.
[0041] The additive components and mass fractions of Examples 1 to 5 and Comparative Examples 1 to 5, and the battery high temperature performance test results are shown in Table 1.
[0042] Among them, 1,3-(1-propylene) sultone is abbreviated as PRS, vinyl sulfate is abbreviated as ESA, vinyl carbonate is abbreviated as VC, vinyl vinyl sulfite is abbreviated as VES, and vinyl sulfite is abbreviated as ES.
[0043] Table 1
[0044]
[0045]
[0046] The internal resistance change rate and capacity retention rate data of the batteries of the embodiments and comparative examples in Table 1 show that, under the same negative electrode compaction density conditions, the combined use of TPPO and the sulfonyl-containing compound has a lower internal resistance change rate and a higher capacity retention rate of the battery, and the sulfonyl-containing compound with a low carbon atom number is beneficial to reducing the internal resistance of the battery; an increase in the negative electrode compaction density will accelerate the increase in the internal resistance of the battery and reduce the cycle performance.
[0047] The negative electrode interface conditions of the batteries of Examples 1 to 5 and Comparative Examples 1 to 5 after low-temperature charging are shown in Table 2.
[0048] Table 2
[0049] Negative electrode interface Example 1 No lithium deposition Example 2 Slight lithium deposition Example 3 Slight lithium deposition Example 4 No lithium deposition Example 5 No lithium deposition Comparative Example 1 Slight lithium deposition Comparative Example 2 Moderate lithium precipitation Comparative Example 3 Severe lithium deposition Comparative Example 4 Severe lithium deposition Comparative Example 5 Slight lithium deposition
[0050] It can be seen from the negative electrode interface conditions of the batteries of each embodiment and comparative example in Table 2 that the negative electrode lithium deposition of the secondary battery manufactured according to Examples 1-5 of the present invention is significantly improved compared with Comparative Examples 2 to 4, indicating that it has better low-temperature charging capability. The reason for the improvement of negative electrode lithium deposition is that the sulfonyl compound with a low number of carbon atoms is selected, and the addition amount does not exceed 3%, which can inhibit the increase of negative electrode impedance and reduce negative electrode lithium deposition.
[0051] It can be seen from Table 1 and Table 2 that the battery of the present invention can still take into account both good high temperature characteristics and low temperature charging capabilities under the condition of having a relatively high negative electrode compaction density.
[0052] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A secondary battery comprising a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte comprises a lithium salt, an organic solvent and an additive, characterized in that: The additives are triphenylphosphine oxide, 1,3-(1-propylene) sultone and vinyl sulfate, wherein the added mass of the triphenylphosphine oxide is 2% of the total mass of the electrolyte, the added mass of the 1,3-(1-propylene) sultone is 0.5% of the total mass of the electrolyte, and the added mass of the vinyl sulfate is 1.5% of the total mass of the electrolyte; Or the additives are triphenyl phosphine oxide, vinyl sulfite and vinyl sulfate, the added mass of the triphenyl phosphine oxide is 2% of the total mass of the electrolyte, the added mass of the vinyl sulfite is 0.5% of the total mass of the electrolyte, and the added mass of the vinyl sulfate is 1.5% of the total mass of the electrolyte; The negative electrode comprises a negative electrode active material and a negative electrode current collector, and the compaction density of the negative electrode except the negative electrode current collector is not less than 1.55 g / cm 3 The positive electrode comprises a positive electrode active material and a positive electrode current collector, and the compaction density of the positive electrode except the positive electrode current collector is not less than 3g / cm 3 .
2. The secondary battery according to claim 1, characterized in that: The compaction density of the negative electrode except the negative electrode current collector is not less than 1.6 g / cm 3 .
3. The secondary battery according to claim 1, characterized in that: The positive electrode and the negative electrode are both capable of absorbing and desorbing lithium ions.
Citation Information
Patent Citations
Additive capable of improving high voltage performance of electrolyte and electrolyte containing additive
CN105186035A
A lithium ion battery electrolyte and a lithium ion battery
CN109065951A
An electrolyte of a non-aqueous lithium ion battery and a lithium ion battery using the electrolyte
CN109216770A
Lithium battery and use of triphenylphosphine oxide as an electrolyte additive therein
WO2018224167A1
